Corrosion induced stress field and cracking time of reinforced concrete with initial defects: Analytical modeling and experimental investigation - Zhang, Xiaogang; Li, Minhui; Tang, Luping; Memon, Shazim Ali; Ma, Guojun; Xing, Feng; Sun, Hongfang (Corrosion Science, 2017)
Abstract This paper presents an analytical model for calculation of corrosion induced stress field and cracking time of concrete cover with initial defects in a reinforced concrete. In the proposed model, two types of initial defects in concrete cover (surface and middle defect) were considered. Experiments were also performed to validate the effectiveness and accuracy of the proposed model. Based on the model analysis, it was found out that initial defects have significant influence on the stress distribution, the corrosion induced expansion pressure in concrete cover, the critical mass of corrosion products, and the cracking time of concrete cover.
Keywords: A. Steel reinforced concrete; B. Cracking time; C. Stress field; D. Corrosion